Friendship in the Momentum of Eid Al-Fitr as an Effort to Build Harmony: A Study of Takhrij and Syarah Hadith - Hasannia, Ali; Nurhuri, Ilvia (Journal of Takhrij Al-Hadith, 2024)
This study aims to discuss the hadith about friendship in the momentum of Eid al-Fitr as an effort to build harmony. This research uses qualitative types through literature studies. The formal object of this research is the science of hadith, while the material object is the hadith about friendship in the narration of Saheeh Bukhari No. 5332. The results and discussion of this study show that the status of hadith of shahih quality meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Imam Bukhari No.5332 is relevant to be used as inspiration in reconnecting relationships that had been severed to be re-established, even not only limited to visiting each other or and limited to repaying each other's kindness but also building harmony and warmth with each other.